Implementation Of Information Technology In Sustainable Building Construction Management - Hatoguan Manurung, Edison; Situmorang, Tiodorus (Khatulistiwa SMART: Science, Methodology, Artificial intelligence, Research, and Technology, 2025)
The construction industry accounts for approximately 36% of global energy consumption and 39% of energy-related carbon emissions, necessitating urgent sustainable transformation through digital technologies. This research aims to analyze and evaluate how information technology implementation can effectively support sustainable construction management by enhancing coordination, improving resource efficiency, reducing environmental impacts, and enabling data-driven decision-making throughout the building lifecycle. The study employs a systematic literature review approach with descriptive analysis, examining 45 peer-reviewed publications from academic databases including Scopus, Web of Science, and Google Scholar published between 2019 and 2025. Data analysis utilized qualitative content analysis techniques to identify recurring themes regarding IT applications in sustainable construction practices. The findings reveal four critical contributions: BIM technology reduces design errors by 40-60% and construction waste by 15-20%; digital project management platforms achieve 12-18% time savings and 8-15% cost reductions; IT-enabled sustainability assessment tools reduce operational energy consumption by 25-35%; and cloud-based collaborative platforms reduce coordination issues by 30-40%. This research demonstrates that integrated information technology systems serve as indispensable enablers of sustainable construction management, offering practical solutions to resource efficiency, environmental impact reduction, and project coordination challenges while maintaining economic viability.